Rates of Hospitalization for Dehydration Following Hurricane Sandy in New Jersey. (10th December 2015) - Swerdel, Joel N.; Rhoads, George G.; Cosgrove, Nora M.; Kostis, John B.
Abstract: Objective: Hurricane Sandy, one of the most destructive natural disasters in New Jersey history, made landfall on October 29, 2012. Prolonged loss of electrical power and extensive infrastructure damage restricted access for many to food and water. We examined the rate of dehydration in New Jersey residents after Hurricane Sandy. Methods: We obtained data from 2008 to 2012 from the Myocardial Infarction Data Acquisition System (MIDAS), a repository of in-patient records from nonfederal New Jersey hospitals (N=517, 355). Patients with dehydration had ICD-9-CM discharge diagnosis codes for dehydration, volume depletion, and/or hypovolemia. We used log-linear modeling to estimate the change in in-patient hospitalizations for dehydration comparing 2 weeks after Sandy with the same period in the previous 4 years (2008–2011). Results: In-patient hospitalizations for dehydration were 66% higher after Sandy than in 2008–2011 (rate ratio [RR]: 1.66; 95% confidence interval [CI]: 1.50, 1.84). Hospitalizations for dehydration in patients over 65 years of age increased by nearly 80% after Sandy compared with 2008–2011 (RR: 1.79; 95% CI: 1.58, 2.02). Conclusion: Sandy was associated with a marked increase in hospitalizations for dehydration. Reducing the rate of dehydration following extreme weather events is an important public health concern that needs to be addressed, especially in those over 65 years of age. ( Disaster Med Public Health Preparedness . 2016;10:188–192)